Solusi Numerik Model SIR pada Penyebaran Penyakit Hepatitis B dengan Metode Perturbasi Homotopi di Provinsi Sulawesi Selatan - Side, Syafruddin; Wahyuni, Maya Sari; Rifki, Muh. (Jurusan Matematika FMIPA UNM, 2020)
This research aims to find out the numerical solustion from a SIR model on the spread of Hepatitis B by Homotopy Perturbation Method. This research used a secundary data from Rosdiana’s research (2015) focused on SIR model and number of Hepatitis B in South Sulawesi 2015 from Health Department of South Sulawesi. The discussion started by determining general solution with Homotopy Perturbation Method, parameter decision, simulation and result analyzis. After conducting an analyzis from numeric simulation it shows that the Homotopy Perturbation Method can be used to analyze the preference of Hepatitis B treatment in South Sulawesi also can be a consideration for preventing action of infectious disease of Hepatitis B. This research gets movement grafic and result analyzis from SIR model by riil data.